Phenomenological Theory and a New Look at Continuity in Architecture - Tourek, Jiří (Actual Problems of Theory and History of Art, 2017)
In the second half of the 20th century, there occurred a gradual but profound change in the view of history in the architectural world. The generation active in post war time (among others Mies van der Rohe) mainly neglected the history of architecture. Starting with the next generation, this attitude radically changed.The important proponents of these changes were to a large extent the architects that were later associated with postmodern architecture. All this is well known.Less known is the role that was played by phenomenology in architecture as a theoretical ground of this change. The article is focused, through an example of Norberg-Schulz’s theories, on the transformation of interest in the history of architecture and on the new understanding of continuity in architecture.What is generally seen as an achievement, i.e. the newly established relation to historical architecture and to built environment, the re-established possibility of inspiration in history, tradition, and continuity withoutbeing necessarily got caught in various historicisms etc., has, nevertheless, the other side. This other side isthe preoccupation with history, the obsession to maintain the status quo of all built environment, the increasein preservation, which can all be observed in large parts of the western civilisation. Thus, the article aims to explore the ambivalent legacy — in terms of relation to history — of some of the phenomenological theories in architecture.
Keywords: phenomenology; architecture; theory; Norberg-Schulz; modernity; preservation